Effects of ginger (Zingiber officinale Roscoe) on DNA damage and development of urothelial tumors in a mouse bladder carcinogenesis model - Bidinotto, Lucas Tadeu; Spinardi-Barbisan, Ana Lucia Tozzi; Rocha, Noeme Sousa; Favero Salvadori, Daisy Maria; Barbisan, Luis Fernando (Wiley-Blackwell, 2006)
Extracts of the spice ginger (Zingiber officinale Roscoe) are rich in gingerols and shogaols, which exhibit antioxidant, anti-inflammatory, antifungal, anti mycobacterial, and anticarcinogenic proprieties. The present study evaluated the chemoprotective effects of a ginger extract on the DNA damage and the development of bladder cancer induced by N-butyl-N-(4-hydroxibutyl) nitrosamine (BBN)/N-methyl-N-nitrosourea (MNU) in male Swiss mice. Groups G1-G3 were given 0.05% BBN in drinking water for 18 weeks and four i.p. injections of 30 mg/kg body weight MNU at 1, 3, 10, and 18 weeks. Group G4 and G5 received only the BBN or MNU treatments, respectively, and groups G6 and G7 were not treated with BBN or MNU. Additionally, Groups G2, G3, and G6 were fed diets containing 1, 2, and 2% ginger extract, respectively, while Groups G1, G4, G5, and G7 were fed basal diet. Samples of peripheral blood were collected during the experiment for genotoxicity analysis; blood collected 4 hr after each MNU dose was used for the analysis of DNA damage with the Comet assay (assay performed on leukocytes from all groups), while reficulocytes collected 24 hr after the last MNU treatment of Groups G5-G7 were used for the micronucleus assay. At the end of the experiment, the urinary bladder was removed, fixed, and prepared for histopathological, cell proliferation, and apoptosis evaluations. Ginger by itself was not genotoxic, and it did not alter the DNA damage levels induced by the BBN/MNU treatment during the course of the exposure. The incidence and multiplicity of simple and nodular hyperplasia and transitional cell carcinoma (TCC) were increased by the BBN/MNU treatment, but dietary ginger had no significant effect on these responses. However, in Group G2 (BBN/MNU/2% ginger-treated group), there was an increased incidence of Grade 2 TCC. The results suggest that ginger extract does not inhibit the development of BBN-induced mouse bladder tumors.
Keywords: ginger; chemoprevention; DNA damage; carcinogen-induced urothelial bladder lesions